2013
DOI: 10.1074/jbc.m113.477281
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Inhibition of Phospholipase C γ2 Adaptor Function Blocks Osteoclastogenesis and Protects from Pathological Osteolysis

Abstract: Background: Genetic deletion of PLC␥2 prevents osteoclast differentiation and reduces bone resorption in vitro and in vivo. Results: Ectopic expression of the tandem SH2 domains of PLC␥2 impairs osteoclastogenesis and protects from bone loss in wild-type mice. Conclusion: Targeting PLC␥2 adaptor function is an efficient strategy to block osteoclast differentiation. Significance: This work provides a framework to design specific PLC␥2 inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
1
6
0
Order By: Relevance
“…The role of the PLCγ isoenzyme in bone resorption and in adhesion receptor signalling of osteoclasts was further emphasized in a recent review reinforcing the statements made by Kertész et al., . Moreover, Dr. Faccio's group provided genetic evidence that targeting PLCγ2 can suppress inflammatory osteolysis . This is in contrast with our observation that PLCγ2 does not play a major role in ovariectomy‐induced bone loss, indicating that inflammatory osteolysis and oestrogen deficiency–triggered bone resorption may utilize different signalling pathways.…”
Section: Phospholipase Cγ2 Is Required For Basal But Not Oestrogen Desupporting
confidence: 84%
“…The role of the PLCγ isoenzyme in bone resorption and in adhesion receptor signalling of osteoclasts was further emphasized in a recent review reinforcing the statements made by Kertész et al., . Moreover, Dr. Faccio's group provided genetic evidence that targeting PLCγ2 can suppress inflammatory osteolysis . This is in contrast with our observation that PLCγ2 does not play a major role in ovariectomy‐induced bone loss, indicating that inflammatory osteolysis and oestrogen deficiency–triggered bone resorption may utilize different signalling pathways.…”
Section: Phospholipase Cγ2 Is Required For Basal But Not Oestrogen Desupporting
confidence: 84%
“…However, an inhibitor that would specifically target the interaction between K15 and PLCγ1, without interfering with the physiological functions of PLCγ1 might counteract only KSHV-dependent signalling processes. Since Decker et al [ 45 ] successfully impaired pathological osteolysis by uncoupling the adaptor and the catalytical functions of PLCγ2 by ectopic expression of tandem PLCγ2 SH2 domains, we used a similar approach and tested the PLCγ2 cSH2 domain as a potential inhibitor of the K15-PLCγ1 interaction. We first characterized the interaction between K15P and the isolated PLCγ2 cSH2 domain in more detail.…”
Section: Resultsmentioning
confidence: 99%
“…We have reported that ablation of PLCγ2 results in a blockade of osteoclastogenesis owing to defective NFATc1 induction (11,22). PLCγ2-deficient mice are osteopetrotic and are also protected from inflammatory osteolysis (23,24).…”
Section: Resultsmentioning
confidence: 99%